Sex-related risk of cardiac involvement in hereditary transthyretin amyloidosis: insights from THAOS - Caponetti, Angelo Giuseppe; Rapezzi, Claudio; Gagliardi, Christian; Milandri, Agnese; Dispenzieri, Angela; Kristen, Arnt; Wixner, Jonas; Maurer, Mathew S.; Garcia-Pavia, Pablo; Tournev, Ivailo; Planté-Bordeneuve, Violaine; Chapman, Douglass; et al. (JACC Heart failure, 2021)
Objectives - Because patients with ATTRv cardiomyopathy are more likely to be male, this analysis aimed to increase information on associations between sex and genotype, phenotype, and degree of myocardial involvement in ATTRv amyloidosis. - Background - Transthyretin amyloid cardiomyopathy is a progressive, fatal disease that occurs due to accumulation of wild-type or variant (ATTRv) transthyretin amyloid fibrils in the myocardium. - Methods - The Transthyretin Amyloidosis Outcomes Survey (THAOS) is an ongoing global longitudinal observational survey of patients with ATTR amyloidosis and asymptomatic carriers with TTR mutations. Data from THAOS (data cutoff: January 6, 2020) were analyzed to determine any sex-based differences in genotype, phenotype, and presence of cardiac and neurological symptoms in patients with ATTRv amyloidosis and in patients with ATTRv amyloidosis and cardiomyopathy. - Results - There were 2,790 patients with ATTRv amyloidosis enrolled in THAOS, with male patients more likely to have symptoms of cardiac involvement and a cardiac phenotype. Male prevalence was greater in patients with more severe cardiac manifestations of disease, as assessed with N-terminal pro-B-type natriuretic peptide, left-ventricular (LV) ejection fraction, mean LV wall thickness divided by height, and LV mass index divided by height. Sex, age at disease onset, and genotype category were identified by multivariate analyses as risk factors for the development of cardiomyopathy (defined as increased LV septum thickness divided by height). - Conclusions - In this analysis, myocardial involvement was more frequent and pronounced in male patients with ATTRv amyloidosis, suggesting that there may be biological characteristics that inhibit myocardial amyloid infiltration in females or facilitate it in males.